2017
DOI: 10.1111/ggi.13069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mini‐Mental State Examination and Montreal Cognitive Assessment executive subtests in detecting post‐stroke cognitive impairment

Abstract: The MoCA executive tasks are more sensitive in detecting executive dysfunction compared with the MMSE executive tasks. Geriatr Gerontol Int 2017; 17: 2329-2335.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Most studies showed an improvement in memory and an increase in MMSE scores [33]. Our results are in line with these results; our study also shows that MOCA-K scores, which can reflect the frontal lobe function, are significantly higher than the scores of other scales and that this difference is higher in the intervention group than in the control group [34,35]. Sub-item analysis of MOCA-K scores showed that the improvement in the executive function and delayed memory was more prominent than that in other domains.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies showed an improvement in memory and an increase in MMSE scores [33]. Our results are in line with these results; our study also shows that MOCA-K scores, which can reflect the frontal lobe function, are significantly higher than the scores of other scales and that this difference is higher in the intervention group than in the control group [34,35]. Sub-item analysis of MOCA-K scores showed that the improvement in the executive function and delayed memory was more prominent than that in other domains.…”
Section: Discussionsupporting
confidence: 92%
“…Studies suggest that the MMSE is an adequate screening instrument in a setting with a high prevalence of disorders resulting in severe cognitive impairment. It loses predictive value when cognitive disturbances are milder, less prevalent, and mainly occur in the executive domain, as seems to be the case in FD …”
Section: Discussionmentioning
confidence: 93%
“…29 Studies suggest that the MMSE is an adequate screening instrument in a setting with a high prevalence of disorders resulting in severe cognitive impairment. It loses predictive value when cognitive disturbances are milder, less prevalent, and mainly occur in the executive domain, [30][31][32] as seems to be the case in FD. 5,6 This is, to our knowledge, the first study on the accuracy and effectiveness of using a cognitive screening instrument in a FD population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most studies have shown overreliance on the Mini-Mental State Examination (MMSE) to measure cognitive function [31], which may limit the possibility of detecting minor cognitive change in various domains. The MMSE has a poor sensitivity for distinguishing mild cognitive impairment due to the insufficient complexity and executive function items [31,37,38]. Compared to the MMSE, the Montreal Cognitive Assessment (MoCA) instrument is a more challenging test that includes higher-level language as well as more complex executive function and visual-spatial processing to enable detection of mild impairment [39,40,41,42].…”
Section: Knowledge Gaps and Recommendations For Future Studiesmentioning
confidence: 99%